Clinical profile of patients with acute pancreatitis in a tertiary care centre in Tripura: A retrospective study - Das, Surajit Kumar; Das, Saswati (Asian Journal of Medical Sciences, 2020)
Background: Acute Pancreatitis is a common disease with wide clinical variation and its incidence is increasing. Acute pancreatitis is an inflammatory process leading to abdominal pain, progressive destruction of exocrine tissue and in some patients a loss of endocrine tissue as well, with multiple organ failure and high mortality. Severity of acute pancreatitis is linked to the presence of systemic organ dysfunction and/or necrotizing pancreatitis. Aims and Objective: The present study was aimed to study the clinical profile of acute pancreatitis, the etiology and complications of acute pancreatitis received treatment in the Department of Surgery, Tripura Medical College & Dr. BRAM Teaching Hospital, Agartala, Tripura. Materials and Methods: This was a hospital based retrospective study which was conducted from January 2019 to December 2019. All patients with a diagnosis of acute pancreatitis were included in this study in order to find out the clinical presentations from the available clinical, laboratory and radiological data. Result: Of the 100 patients in this study, 96 were male and 4 were female. Minimum age in our study was 10 years and maximum were 70 years. Maximum numbers of patients were below 45 years of age. Alcohol was identified as the most important etiological factor associated with acute pancreatitis. Among the known etiological factors 90% of the cases were related to alcoholism and 4% were due to gall stone disease. Abdominal pain and vomiting were the most common symptoms in our study. Epigastric tenderness was present in 90% of the cases and guarding/rigidity in 50% of cases. 14% patients showed jaundice as a sign of acute pancreatitis. There was no major difference between the CT grading system and clinical grading system. Most of the patients recovered with conservative treatment. Adverse outcome was noted in one patient with acute necrotizing pancreatitis. Conclusion: Acute pancreatitis is one of the leading causes of increase in morbidity and mortality to society. Clinical assessment along with radiological findings correlated well with the morbidity and mortality. Our study identifies alcoholism as one of the most important etiological factors.